Gambogic acid suppresses osteosarcoma progression through upregulation of FOXO3a - Yawei Hu; Jiawen Wu; Songqing Ye; Hao Zhang; Zengfeng Guo; Xiaohong Han; Jianhua Zhou (Discover Oncology)
Abstract Background Osteosarcoma is a prevalent bone cancer in children and adolescents, posing significant treatment challenges due to its high metastatic potential and resistance to traditional chemotherapy. Gambogic Acid (GA), a natural compound, has demonstrated promising anticancer properties, including inhibition of cell proliferation and induction of apoptosis. Methods This study evaluated the anticancer effects of GA on osteosarcoma cell lines 143B and U2OS through cell viability assays, proliferation tests, wound healing assays, and flow cytometry to assess migration and apoptosis. RNA sequencing and RT-qPCR analyses were conducted to identify molecular mechanisms, with a focus on the tumor suppressor transcription factor FOXO3a. siRNA-mediated knockdown of FOXO3a was performed to determine its role in GA’s mechanism of action. Results GA treatment significantly reduced cell viability and proliferation in a dose- and time-dependent manner, as shown by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and CCK-8 assays. Wound healing assays revealed a marked inhibition of cell migration, while flow cytometry confirmed a significant increase in apoptosis rates following GA treatment. RNA sequencing identified FOXO3a as a key upregulated gene in both cell lines after GA exposure, which was validated by RT-qPCR. Importantly, FOXO3a knockdown diminished GA's effects on cell viability, migration, and apoptosis, underscoring its pivotal role in mediating GA's anticancer activity. Conclusions The findings suggest that GA exerts potent anticancer effects on osteosarcoma cells through the upregulation of FOXO3a, a critical tumor suppressor. These results provide a foundation for further exploration of GA as a novel therapeutic agent for osteosarcoma, potentially offering a safer alternative to conventional chemotherapy. Future research will aim to elucidate the detailed mechanisms underlying the interaction between GA and FOXO3a and to optimize GA-based therapeutic strategies.